PENGEMBANGAN HAK KEKAYAAN INTELEKTUAL SEBAGAI COLLATERAL (AGUNAN) UNTUK MENDAPATKAN KREDIT PERBANKAN DI INDONESIA - Sri Mulyani (Faculty of Law, Universitas Jenderal Soedirman, 2012)
Intellectual Property Rights is granted the exclusive rights to creators, inventors or designers for the creation or invention that has commercial value, either directly or through the automatic registration of the relevant agencies as awards, recognition should be given the protection of the rights of the community development law. Globally, the IPR will be used as collateral to obtain a bank loan internasional. In this law is necessary to realize the concept of legislation in each country who are willing to apply that regulate substance loading, binding, and registration of intellectual property as collateral. Key words: development of intellectual property rights, collateral, bank credit in Indonesia